KEDUDUKAN PERSONAL GUARANTEE DALAM MEMBERIKAN JAMINAN KEPADA KREDITUR ATAS FASILITAS KREDIT YANG DIPEROLEH OLEH DEBITUR TERKAIT PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Annisa Rizkika Chairiza Nst; Tan Kamello, Suprayitno (INTELIGENSIA MEDIA, 2024)
This article will introduce an investigation into Indonesian regulations relating to the responsibilities and implementation of PKPU. The research was carried out by using a library research strategy, especially library research, by collecting and focusing on scientific books, writings, logical works, legal guidelines, and other readings related to the preparation of this research, and the archives contained in it. referred to is a decision in court. Examination of information in this research was carried out subjectively; This means that the information obtained is then entered deliberately and then broken down subjectively to achieve clarity on the problem being studied. This research is descriptive analytical in nature, revealing legal guidelines related to legitimate speculation which is the object of exploration, as well as the implementation of PKPU regulations in the eyes of the public. The information audit strategy is used to convey information that explains scientifically, namely what has been regulated in the laws and regulations related to PKPU and then investigates the actual practices that occur in the field, such as those investigated and focused on in general. The results of the research explain that individual guarantors should not act as respondents in PKPU. The legal consequence is that a guarantor who has waived his privileges is considered to have bound himself together with the main debtor, but the context of the waiver of privileges is only for confiscation in bankruptcy, not for PKPU